Juridical Analysis of Non-Compliance and Implications with South Kalimantan Regional Regulation on Mining Activities - Brigitta Kezia Eijileen; Katya Aiko Kusuma; Kesya Chantall Alisya Deru (Jurnal Hukum Prasada, 2025)
In accordance with the law of regional regulations of Kalimantan Selatan number 5 year 2019 that caused a deep legal impact in regard to the legality of operation of mining in the regulated area. Practice such as mining without permit (PETI), forgery of permit, violation of the environment and/or land grabbing outside of the claim reflects the structural weakness in law enforcement and governance. This issue can cause legal uncertainty and credibility of the framework of regional regulations. Further violations in a broader sense also have a direct impact on the trust of investors in the local sector because of its legal uncertainty, unhealthy business competition and risk of environment and social aspect. Investors will think twice and hesitate on investing even if South Kalimantan is rich in mineral and mining sources, due to the weak law enforcement, risk, reputation and future potential conflict regarding areas and permit. As investors prefer a legal certainty to protect their rights, fair competition and predictable jurisdictions. If there is no thorough reformation, healthier institution coordination and improved enforcement mechanism, South Kalimantan will have a chance of economic and ecological setback in a long period of time that can weaken the appeal of the mining industry.